Eccrine and Apocrine Carcinoma in Dogs - Nascimento de Figueiredo Martins, Yanna; Guedes Sampaio, Rubia Avlade; da Silva Barbosa, Maria Joyce; Dantas de Gois, Daniela; Ferreira da Silva Neto, José; Queiroz Franco, Camila Ingrid; Barbosa de Lucena, Ricardo (Acta Scientiae Veterinariae, 2020)
Background: Sweat gland carcinomas divide into eccrine, apocrine, mixed origin (eccrine and apocrine). Eccrine carcinoma (EC) is a rare malignant neoplasm of the sweat glands that can affect dogs, cats, and humans. EC can present itself as a solitary swelling in the pads, digits, or distal limbs. EC is more common in elder animals, and exhibits no predisposition according to breed. In humans, EC is more frequent in the head and neck, and is more likely to occur in mid-aged people; metastases can develop in any site of the body. A diagnosis of this type of tumor can be determined by histopathological examination. Apocrine carcinomas occur most frequently in the axillary areas even though they may occur in other regions of the body, and affect mainly elder animals. Case: A 13-year-old male mongrel dog with a history of presence of smooth reddish infiltrative nodule in the skin of the thorax, but with no history of progression, was examined. After running complementary tests, a fragment of the skin on the thorax was taken for biopsy. The second animal was an 8-year-old female Golden Retriever, which was presented with a history of presence of a nodule on the right digital pad. After running complementary tests, a fragment of this nodule was collected. In both cases, the excised fragments were placed in 10% buffered formalin and routinely processed for the preparation of histological slides, which were stained with hematoxylin and eosin, and subjected to histopathological evaluation. Light microscopy analysis revealed, in both cases, the presence of a poorly delimited, non-encapsulated mass infiltrating the muscle and adipose tissue. Necrotic areas, and presence of eosinophilic material in the nucleus were observed. Additionally, the samples from both cases were subjected to immunohistochemical staining for cytokeratin (CK Pan). Discussion: A definitive diagnosis of sweat gland carcinoma was achieved by means of the histopathological analysis. Sweat gland neoplasms are uncommon and difficult to diagnose; distinguishing eccrine carcinoma from apocrine carcinoma requires knowledge on the site of origin of the tumor. Some authors assert that, in spite the growing number of reports on tumors of cutaneous glands in dogs, there are only few immunohistochemical studies on cutaneous gland neoplasms in these animals. There is no specific immunohistochemical marker to distinguish eccrine carcinoma from apocrine carcinoma. Consequently, investigation on the anatomical origin of the tumor is important. In the cases describe herein, involvement of the thorax (apocrine) and digital pad (eccrine) are reported. However, there are accounts of the occurrence of sweat gland tumors in axillary and inguinal regions, as well as in the limbs. Both biopsy samples tested positive for cytokeratin (CK) after immunohistochemical examination. This marker is specific for simple epithelium and, according to some authors, can distinguish an eccrine carcinoma from basal cell carcinoma. The antibody used did not stain the innermost are of the tumor, where cells may be negative for CK. Some tumors may not have specific markers, which makes a combination of clinical data and complementary histopathological and immunohistochemical exams necessary for the determination of a diagnosis, as is the case for eccrine and apocrine carcinomas. In view of the scarcity of reports on eccrine carcinoma in the literature, and considering the small number of immunohistochemical studies on cutaneous gland tumors in dogs and cats, this work can help the determination of the diagnosis of cutaneous neoplasms, which are frequently observed in the clinical routine.